Seniors’ attitudes to voicing complaints: a qualitative study - Grougiou, V.; Pettigrew, Simone (Routledge, 2010)
Demographic trends and developments in the societal distribution of financial resources have resulted in a substantial increase in the purchasing power of the senior market, making this segment of increasing interest to marketers. This qualitative study examined seniors’ knowledge of and attitudes towards voicing complaints to service providers. In-depth interviews and projective techniques were conducted with 60 seniors of varying demographic profiles. The findings support previous research that has found that seniors may avoid expressing dissatisfaction with service organisations directly to the service provider. Interviewees attributed their reluctance to complain to image management concerns, culturally-attributed difficulties, market alienation, emotional and physical costs, and prior disappointing experiences. A model of senior customers’ intentions to voice their complaints to service organisations is proposed and suggestions for further research are provided.